Ancestral and offspring nutrition interact to affect life-history traits in Drosophila melanogaster. Issue 1897 (27th February 2019) - Deas, Joseph B.; Blondel, Leo; Extavour, Cassandra G.
Abstract : Ancestral environmental conditions can impact descendant phenotypes through a variety of epigenetic mechanisms. Previous studies on transgenerational effects in Drosophila melanogaster suggest that parental nutrition may affect the body size, developmental duration and egg size of the next generation. However, it is unknown whether these effects on phenotype remain stable across generations, or if specific generations have general responses to ancestral diet. In the current study, we examined the effect on multiple life-history phenotypes of changing diet quality across three generations. Our analysis revealed unforeseen patterns in how phenotypes respond to dietary restriction. Our generalized linear model showed that when considering only two generations, offspring phenotypes were primarily affected by their own diet, and to a lesser extent by the diet of their parents or the interaction between the two generations. Surprisingly, however, when considering three generations, offspring phenotypes were primarily impacted by their grandparents' diet and their own diet. Interactions among different generations' diets affected development time, egg volume and pupal mass more than ovariole number or wing length. Furthermore, pairwise comparisons of diet groups from the same generation revealed commonalities in strong responses to rich versus poor diet: ovariole number, pupal mass and wing length responded more strongly to poor diet than to rich diet, while development time responded strongly to both rich and poor diets. To improve investigations into the mechanisms and consequences of transgenerational, epigenetic inheritance, future studies should closely examine how phenotypes change across a higher number of generations, and consider responses to broader variability in diet treatments.